The desirability of Integrated Influential Factors (IIFs) model of internal stakeholder as a panacea to project completion delay in Yemen - AL-Fadhali, Najib; Zainal, Rozlin; Kasim, Narimah; Dodo, Mansir; Ng, Kim Soon; Ali Hasaballah, Abdel Hafiz (Taylor and Francis, 2019)
In Yemen and other developing countries, many construction projects experience extensive delays by exceeding their initial completion time thereby leading to several reported effects which among others include: cost overrun; litigation; arbitration; failure; and abandonment. Although variability in prevailing conditions warrants influential factors causing such delays to differ among countries, an oft-cited approach implemented to mitigate these effects is enhancing the collaboration of stakeholders in construction project delivery. While this approach is overwhelmingly applauded by researchers, there however exist scant studies focusing on how effective project internal stakeholder integration can potentially impact prompt construction project delivery particularly in developing countries. This study as such, seeks to propose an Integrated Influential Factor (IIF) model of internal stakeholders with a view to reduce delay in construction project delivery. Data was collected from 301 respondents based on the influential factors divided into 7 categories of internal stakeholders. Findings from analysed results (using IBM SPSS Statistics 23.0 and IBM SPSS AMOS SEM Version 23) were used to develop the Integrated Influential Factors (IIF) Model of Internal Stakeholder in Yemen Construction Industry. The proposed model was validated through construction industries expert opinion which inform that sincere and concerted effort towards effective management of the studied factors could not only stem down their adverse effect on project completion delay but equally enhance construction project implementation if the model is tenaciously implemented.